Studies on abscisic acid in reproductive buds of Prunus persica cv. Goosen - Jurisch, Christopher T.(Christopher Theodor) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1971.